Estrogenic Compounds Impair Primordial Follicle Formation by Inhibiting the Expression of Proapoptotic Hrk in Neonatal Rat Ovary. Issue 4 (1st October 2016) - Zhang, Haolin; Nagaoka, Kentaro; Usuda, Kento; Nozawa, Kaori; Taya, Kazuyoshi; Yoshida, Midori; Watanabe, Gen
Abstract: Exposure to endocrine-disrupting chemicals (EDCs) during fetal and neonatal periods can have toxic effects that are irreversible and last a lifetime. However, the mechanism underlying this phenomenon is still unknown. Here, we show the effect of 17alpha-ethynyl estradiol (EE) on the development of the primordial follicle during early ovarian development in female rats. Microarray analysis revealed the down-regulation of Hrk, an activator of apoptosis, in neonatal ovaries exposed to EE. Real-time PCR analysis also showed a decrease of Hrk mRNA expression in ovaries treated with EE both in vitro and in neonatal rats. An immunostaining assay showed that HRK protein and cleaved caspase 3 colocalize in the oocytes at Postnatal Day 1 (PND1). The EE-exposed ovaries had a reduced number of oocytes positive for TUNEL staining compared to control ovaries at PND1. Abnormal follicle formation of EE-exposed ovaries was observed at PND7 and PND21. A TUNEL staining assay revealed that Hrk depletion reduced the number of apoptotic oocytes. In addition, down-regulation of Hrk mRNA expression was observed in ovaries treated with other estrogenic chemicals. We propose a model in which EE inhibits oocyte apoptosis in the neonatal ovary by suppressing the expression of Hrk, thereby disrupting follicle formation and ovary function.